2016
DOI: 10.1007/s00737-016-0705-6
|View full text |Cite
|
Sign up to set email alerts
|

Childhood sexual abuse, intimate partner violence during pregnancy, and posttraumatic stress symptoms following childbirth: a path analysis

Abstract: The aim of the study was to explore the pathways by which childhood sexual abuse (CSA), psychological and physical intimate partner violence (IPV) during pregnancy, and other covariates relate to each other and to posttraumatic stress disorder (PTSD) symptoms in the postpartum period. The sample comprised 456 women who gave birth at a maternity service for high-risk pregnancies in Rio de Janeiro, Brazil, interviewed at 6-8 weeks after birth. A path analysis was carried out to explore the postulated pathways be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 73 publications
3
20
0
Order By: Relevance
“…Consistent with the existing literature, 3,20,21 the present study showed that women with a history of abuse reported higher CityBiTS scores. Similarly, in accordance with past findings, 6,9,[20][21][22] we found that psychiatric medication intake before pregnancy was associated with higher PTSD scores. Therefore, women with a history of abuse and psychiatric medication intake before pregnancy should be closely followed and screened for PP-PTSD.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with the existing literature, 3,20,21 the present study showed that women with a history of abuse reported higher CityBiTS scores. Similarly, in accordance with past findings, 6,9,[20][21][22] we found that psychiatric medication intake before pregnancy was associated with higher PTSD scores. Therefore, women with a history of abuse and psychiatric medication intake before pregnancy should be closely followed and screened for PP-PTSD.…”
Section: Discussionsupporting
confidence: 91%
“…Financially disadvantaged individuals often prefer to live as a part of large families. Consistent with the existing literature, 3,20,21 the present study showed that women with a history of abuse reported higher CityBiTS scores. Similarly, in accordance with past findings, 6,9,20‐22 we found that psychiatric medication intake before pregnancy was associated with higher PTSD scores.…”
Section: Discussionsupporting
confidence: 91%
“…The literature on risk factors for PPD, including low social support [25], low social economic status [26], cigarette smoking [27], low sleep quality [28,29], unplanned pregnancy [26], and intimate partner violence [30] is substantial. The potential risk factors for PP-PTSD include childhood sexual abuse [31], intimate partner violence [31], low social support [32], instrumental birth, and caesarean section [33,34]. Indeed, the potential risk factors that have been identified and tested in other countries or regions have not been thoroughly investigated in China.…”
Section: Introductionmentioning
confidence: 99%
“…To regain a feeling of safety, women-survivors of CSA may seek a means to control the situation and therefore cope with feelings of threat or disempowerment during their maternity care. Although the literature-base is small (Montgomery, 2013), scholars have written regarding women's experiences of childbearing after CSA and how they cope during times of distress when engaging with maternity care services (Gaudard e Silva de Oliveira et al, 2016;Leeners et al, 2016). These ways of coping are crucial to maintaining a sense of control in situations in which they feel they have none (Byrne et al, 2017;Montgomery et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%